THE IMPACT OF BARIATRIC SURGERY ON ORAL HEALTH - Gubetti, Gabriele; Bona, Vitor Schweigert (Seven Editora, 2025)
This study explores the impact of bariatric surgery on oral health, highlighting the importance of the dental surgeon in the multidisciplinary team for the pre- and postoperative follow-up of these patients. Through a literature review, studies were analyzed that relate bariatric surgery to dental complications, such as reflux, vomiting, vitamin deficiency, xerostomia and dental erosion. The results show the vulnerability of bariatric patients to these conditions, reinforcing the need for constant dental follow-up. It is concluded that the integration of the dental surgeon in the team is essential to prevent and treat these complications, promoting a better quality of life for patients.DOI: https://doi.org/10.56238/sevened2024.037-188